Pengembangan Kesejahteraan Lansia Rw.19 Sendangmulyo Semarang - Dewi, Rusmalia - (TEMATIK, 2023)
Abstrak Tujuan pengabdian masyarakat ini adalah upaya melatih kesejahteraan lansia melalui kadernya di RW.19 Sendangmulyo di kota Semarang. Posyandu Lansia di RW.19 Sendangmulyo berupaya memelihara, mempertahankan, dan mengembangkan nilai-nilai budaya yang dilaksanakan melalui upaya peningkatan kesejahteraan sosial bagi para lanjut usia yang bertujuan mewujudkan kemandirian dan kesejahteraan para lanjut usia.Target khususnya adalah para lansia mampu beraktivitas secara mandiri, dengan melakukan pelatihan kepada para kader lansia diharapkan dapat mendistribusikan ilmu yang diperoleh untuk para lansia yang berada di lingkungan mereka. Hal ini selaras dengan Rencana Aksi Nasional Kesehatan Lanjut Usia Tahun 2016-2019, Pemerintah Pusat dan Pemerintah Daerah dapat melibatkan peran serta lintas sektor dan masyarakat. Peran serta lintas sektor dan masyarakat dapat dilakukan pada tahap penyusunan, pelaksanaan, pemantauan, dan evaluasi. Salah satu peran yang tim kami lakukan adalah memberikan pelatihan terkait kesejahteraan Lansia. Tim pengabdian memberikan pelatihan terkait kesejahteraan lansia dengan metode pembelajarannya berupa ceramah, cerita, permainan dan diskusi bersama. Evaluasi singkat yang dilihat oleh tim pengabdian menunjukkan bahwa para kader lansia menyimak dengan baik pemberian materi yang diberikan, mereka dapat menyerap ilmu yang diberikan dan menambah pengetahuan mereka tentang kebahagiaan pada lansia. Para kader lansia ini juga berdiskusi bersama para lansia yang hadir beserta tim pengabdian. Kami saling bersinergi memberikan arahan dan masukan agar para lansia ke depan menjadi lebih mandiri dan bahagia dalam beraktifitas sehari-hari. Hasil pengabdian kami melalui hasil pre-test dan post-test menunjukkan para kader lansia mampu memahami hasil pelatihannya dan siap mendistribusikan pada lansia-lansia yang berada di lingkungan RW.19 Sendangmulyo. Kata kunci: Kesejahteraan Lansia, Kader Lansia, Lansia RW 19 Abstract The purpose of this community service is to train the welfare of the elderly through their cadres at RW.19 Sendangmulyo in the city of Semarang.The Elderly Posyandu in RW.19 Sendangmulyo seeks to maintain, maintain, and develop cultural values which are carried out through efforts to improve social welfare for the elderly with the aim of realizing independence and welfare for the elderly. The specific target is that the elderly are able to move independently, by conducting training for elderly cadres it is hoped that they will be able to distribute the knowledge gained to the elderly in their environment. This is in line with the 2016-2019 National Action Plan for Elderly Health, where the Central Government and Regional Governments can involve cross-sectoral and community participation. Participation across sectors and the community can be carried out at the stages of preparation, implementation, monitoring and evaluation. One of the roles that our team performs is to provide training regarding the welfare of the elderly. The service team provides training regarding the welfare of the elderly with learning methods in the form of lectures, stories, games and joint discussions. The brief evaluation seen by the community service team shows that the elderly cadres pay close attention to the material provided, they can absorb the knowledge provided and add to their knowledge about happiness in the elderly. These elderly cadres also discussed with the elderly who were present along with the service team. We synergize with each other to provide direction and input so that the elderly in the future will become more independent and happy in their daily activities. One of the roles that our team performs is to provide training regarding the welfare of the elderly. The service team provides training regarding the welfare of the elderly with learning methods in the form of lectures, stories, games and joint discussions. The brief evaluation seen by the community service team shows that the elderly cadres pay close attention to the material provided, they can absorb the knowledge provided and add to their knowledge about happiness in the elderly. These elderly cadres also discussed with the elderly who were present along with the service team. We synergize with each other to provide direction and input so that the elderly in the future will become more independent and happy in their daily activities. The results of our service through the results of the pre-test and post-test show that the elderly cadres are able to understand the results of their training and are ready to distribute them to the elderly who are in the RW.19 Sendangmulyo environment. Keywords: Elderly Welfare, Elderly Cadre, Elderly RW 19